CIRCULAR ECONOMY PRACTICES IN AGRICULTURE: REVITALIZING ENVIRONMENTAL HEALTH AND CULTURAL HERITAGE IN WEST JAVA - Ernah (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
Transformation going to economy circular in sector agriculture become a key strategy for reach development sustainable environment. In West Java, an area rich in diversity life and culture agrarian, implementation principal economy circular No only contribute to efficiency source power and reduction waste, but also plays a role important in preservation environment and revitalization values wisdom local. This article review literature latest about practice economy circular in the field agriculture, with focus on the approaches that have been implemented in West Java, including utilization waste organic, agriculture integrated, and use technology appropriate use based on community. In addition, articles it also discusses challenge implementation, potential improvement quality environment, as well as his contribution to preservation culture local. Results of the study show that integration between innovation technology, policy area, and participation public become key in push system agriculture adaptive and sustainable circular.